Diabetes and Exercise From Pathophysiology to Clinical Implementation (Contemporary Diabetes,, 2018)
Now in a fully revised and updated second edition, written and editing by leading experts in the field, this comprehensive and practical text brings together the latest guidelines and recommendations on the benefits of exercise and physical activity in the management of diabetes and its complications, providing both the researcher and practitioner with evidence-based information that is both theoretically and clinically useful. Part one sets the stage by discussing the epidemiology and prevention of type 2 diabetes and the metabolic syndrome. The physiological effects of exercise in type 2 diabetes are covered in part two, covering molecular mechanisms, adiposity, sex differences, cardiovascular consequences and musculoskeletal changes. Part three addresses practical issues that are essential in order to safely engage patients with diabetes in exercise-related research protocols and clinical programs, including DPP and LOOK Ahead, nutrition, behavioral changes, and guidelines for exercise testing. The final section examines special considerations for exercise in people with diabetes, such as those with neuropathy, cardiac issues and peripheral artery disease. Taken together, Diabetes and Exercise, Second Edition brings together the latest information and thought leaders in the field to create a unique and useful text for all clinicians, researchers and therapists working to integrate physical activity into their management strategies for the increasing number of diabetic patients.